Why Does So Matter to Be a Dead Person? - A. V. Nekhaev (Омский научный вестник: Серия "Общество. История. Современность", 2021)
According to animalism we are identical with human animals. Our death coincides with the cessation of the functioning of an organism. Biological approach to personal identity seems to imply that the corpse causally connected to me (as an organism) is not me. In other words, there is no such an entity as a human animal that later becomes a corpse. It is so-called «the corpse problem». However, there are various views compatible with animalism, for instance the thesis that after death we can survive as corpses or souls. The main task of the article provides a critical analysis of these views